2014
DOI: 10.1002/pmic.201300402
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of potential prognostic biomarkers in resectable pancreatic ductal adenocarcinoma

Abstract: Pancreatic cancer is a devastating disease with a mortality rate almost identical with its incidence. In this context, the investigation of the pancreatic cancer proteome has gained considerable attention because profiles of proteins may be able to identify disease states and progression more accurately. Therefore, our objective was to investigate the changes in the proteome of patients suffering from pancreatic ductal adenocarcinoma (PDAC) by a comprehensive quantitative approach. Comparative proteomic profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…The analysis was performed on 95 proteins with 2-fold higher expression in the HFB system when compared to those in the MNC system. Upregulated proteins were selected for this analysis because they should be more suitable as for potential biomarkers (22). The upregulated proteins could form at least three clusters of the interaction networks as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis was performed on 95 proteins with 2-fold higher expression in the HFB system when compared to those in the MNC system. Upregulated proteins were selected for this analysis because they should be more suitable as for potential biomarkers (22). The upregulated proteins could form at least three clusters of the interaction networks as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous proteomic studies in pancreatic tissue were mainly focused on finding biomarkers of pancreatic cancer 31,32 . At least 40% of the differentially expressed proteins were common in chronic pancreatitis and pancreatic ductal adenocarcinoma (PDAC), a common pancreatic cancer 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…We performed an integrative meta-analysis on pancreatic cancer secretome and proteome data to identify clinically relevant diagnostic and prognostic biomarkers. According to the meta-analysis study design and inclusion and exclusion criteria (Figure 1), 20 secretome studies and 35 proteome studies in pancreatic cancer were selected, which reported protein data obtained by mass spectrometry (Tables 1 and 2) [3,6,29,34,37,41,43,[45][46][47]. These data identified 782 proteins in pancreatic cancer secretome and 517 proteins in pancreatic ductal adenocarcinoma tumor samples.…”
Section: Integration Of Secretome and Proteome Meta-analysis Identifimentioning
confidence: 99%